2017
DOI: 10.3928/00989134-20170111-01
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Nursing Leadership Education in Long-Term Care: Intervention Design and Evaluation

Abstract: The main objective of the current case study was to investigate the perceived leadership learning needs and feasibility of delivering leadership education to registered staff involved in direct care in long-term care (LTC) homes. The study was conducted in Ontario, Canada, and participants included RNs, registered practical nurses, and nursing administrators. Phase 1 bilingual web-based survey and bilingual focus group needs assessment data supported a preference for external training along with in-house mento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…The current system is designed to admit and discharge patients to discrete intensive environments. Episode-based payments lead to hospitals pushing patients out the door quicker and sicker, while SNFs react to business models with heavier ratios of patients to RNs supported by LPNs and CNAs (Clark et al, 2017;Fiset, Luciani, Hurtubise, & Grant, 2017;Vasilevskis et al, 2017). The current study identified that hospital nurses are often silent partners in transitional care decision making and continuity of care discussions with SNF care providers.…”
Section: Discussionmentioning
confidence: 87%
“…The current system is designed to admit and discharge patients to discrete intensive environments. Episode-based payments lead to hospitals pushing patients out the door quicker and sicker, while SNFs react to business models with heavier ratios of patients to RNs supported by LPNs and CNAs (Clark et al, 2017;Fiset, Luciani, Hurtubise, & Grant, 2017;Vasilevskis et al, 2017). The current study identified that hospital nurses are often silent partners in transitional care decision making and continuity of care discussions with SNF care providers.…”
Section: Discussionmentioning
confidence: 87%
“…One high-relevance study found statistically significant improvement in an objective measure of team leadership skills by paediatric residents participating in a leadership workshop 31. Various other studies using self-report to measure confidence or use of specific leadership/management skills also found improvements after a training programme 50–62. Note that all articles relying only on self-report were considered ‘low relevance’ for the purposes of answering the research question and should not be considered strong evidence of a benefit to the organisation.…”
Section: Resultsmentioning
confidence: 99%
“…Only two of the intervention studies were initiated as a result of the direct learning needs of the caregivers. [38,39] In three studies, the intervention took place in a workplace context, [38,40,41] in six studies the intervention was outside the workplace, with a followup in the workplace context, [42][43][44][45][46][47] and the majority of the interventions took place completely outside the workplace.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[38,42,45,55] Residents' complex behaviors made learning among caregivers challenging, as some forgot what they had learned and others were not comfortable speaking about or sharing their thoughts. [43,44,52] The same challenging situations can also trigger learning, when caregivers are, for example, eager to learn in order to relieve a resident's distress, share experiences, and reflect alone or together. [35,43,46,51] Other emotions that influence WBL are courage and confidence, in combination with sharing and social support.…”
Section: Individual Learningmentioning
confidence: 99%